(untitled) (Global Journal of Human-Social Science, 2021)
Under the basic premise that an economy and its territory as a socioeconomic entity, are inscribed into a nation’s space. Accordingly, the concomitant sustainable handling of its natural resources and people´s well-being depends on myriad factors among which stands out firstly, the country’s own socioeconomic dynamics and secondly, but not least important, the political capacity of the State´s intervention into the economy, as the foremost legal entity capable to advance the nation´s economic strategy, to simultaneously foment growth and social well-being into the nation. Upon this premise, the article aims at analyzing the socioeconomic implications and multiple externalities derived from the neoliberal economic strategy implemented by Mexico in the last decades, with particular reference to the country´s current urban imbalances around the country´s top 15 municipalities including Mexico City to demonstrate its failure and the compelling need to reorient it towards a more balanced, social-inclusive and sustainable urban development. Time´s horizon for this analysis ranges from 1980-2018.